Longitudinal monitoring of disease burden and response using ctDNA from dried blood spots in xenograft models. Issue 8 (13th June 2022) - Sauer, Carolin M; Heider, Katrin; Belic, Jelena; Boyle, Samantha E; Hall, James A; Couturier, Dominique‐Laurent; An, Angela; Vijayaraghavan, Aadhitthya; Reinius, Marika AV; Hosking, Karen; Vias, Maria; Rosenfeld, Nitzan; et al.
Abstract: Whole‐genome sequencing (WGS) of circulating tumour DNA (ctDNA) is now a clinically important biomarker for predicting therapy response, disease burden and disease progression. However, the translation of ctDNA monitoring into vital preclinical PDX models has not been possible owing to low circulating blood volumes in small rodents. Here, we describe the longitudinal detection and monitoring of ctDNA from minute volumes of blood in PDX mice. We developed a xenograft Tumour Fraction (xTF) metric using shallow WGS of dried blood spots (DBS), and demonstrate its application to quantify disease burden, monitor treatment response and predict disease outcome in a preclinical study of PDX mice. Further, we show how our DBS‐based ctDNA assay can be used to detect gene‐specific copy number changes and examine the copy number landscape over time. Use of sequential DBS ctDNA assays could transform future trial designs in both mice and patients by enabling increased sampling and molecular monitoring. Synopsis: A novel approach is developed for longitudinal monitoring of tumour burden in patient‐derived xenograft (PDX) models using dried blood spots from minute volumes of blood. Circulating tumour DNA (ctDNA) can be detected in minute volumes of blood ( 50 µl) collected as dried blood spots (DBS) from the tail vein in PDX mice. The xenograft Tumour Fraction (xTF) is calculated using species‐specific alignment of reads obtained from shallow whole‐genome sequencing of DBS samples. The xTF metric allows accurate monitoring of disease progression over time. The xTF rate of change during the first 30 days of treatment is predictive of disease outcome in PDX mice. Abstract : A novel approach is developed for longitudinal monitoring of tumour burden in patient‐derived xenograft (PDX) models using dried blood spots from minute volumes of blood.